Developing a business simulation game: integrating multiple development tools - Williams, Robert; Klass, Des (The Informing Science Institute, 2007)
In most cases today information systems development involves the use of multiple developmenttools. The developer has the choice of many competing vendor tools to choose from, and thechoices to be made are complex. Will the various tools work together, and which tool should bechosen for which task? This paper describes the development of a business simulation game, andthe role various development tools played in the process. The reasons, and how the tools wereused, are also discussed.